2021
DOI: 10.1016/j.medj.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Isotope tracing reveals glycolysis and oxidative metabolism in childhood tumors of multiple histologies

Abstract: Background: Survival among children with high-risk solid tumors remains poor. Reprogrammed metabolism promotes tumor growth and may contain therapeutic liabilities. Tumor metabolism has been assessed in adults using intra-operative 13 C-glucose infusions. Pediatric tumors differ from adult cancers in their low mutational burden and derivation from embryonic tissues. Here, we used 13 C infusions to examine tumor metabolism in children, comparing phenotypes among tumor types and between childhood and adult cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 47 publications
(92 reference statements)
0
20
0
Order By: Relevance
“…Multiple drugs are in development in other tumors that target the urea cycle through inhibition of aspartate or ASS1 [ 72 , 73 ], and some of these agents could be applied to medulloblastoma tumors with vulnerable metabolic profiles. Recent publications suggest that clinical metabolic profiling can be performed on pediatric primary tumor samples, suggesting that targeting metabolic profiles could be a new frontier in pediatric cancer and in brain tumors in general [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple drugs are in development in other tumors that target the urea cycle through inhibition of aspartate or ASS1 [ 72 , 73 ], and some of these agents could be applied to medulloblastoma tumors with vulnerable metabolic profiles. Recent publications suggest that clinical metabolic profiling can be performed on pediatric primary tumor samples, suggesting that targeting metabolic profiles could be a new frontier in pediatric cancer and in brain tumors in general [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the same approach of stable-isotope tracing in culture, in vivo flux analysis differs by the fact of requiring intravenous infusion of 13 C and later tissue collection. There are no established protocols for 13 C infusion regimen targeting bone tissue but, intra-operative 13 C-glucose infusions in humans subjects showed sufficient tracing resolution in osteosarcoma samples ( Johnston et al, 2021 ). This suggests that in vivo flux analysis can potentially be used to perform metabolic tracing in bone tissue, having an important applicability in understanding how different mouse models and signaling manipulations can impact bone metabolism ( Sanchez-Arago et al, 2013 ; Lee et al, 2019 ; Hollenberg et al, 2020 ; Pattappa et al, 2011 ; Forni et al, 2016 ).…”
Section: Methods To Study Bioenergetics On a Subcellular Cellular And...mentioning
confidence: 99%
“…Infusion of [U-13 C]glucose in patients revealed distinct metabolic fates depending on the tumor type. A recent study has reported that pediatric solid tumors use both glycolysis and the TCA cycle in vivo, with subtype-specific differences observed in glucose handling (Johnston et al, 2021).…”
Section: Implementing Tumor Metabolic Profiling For Clinical Decision...mentioning
confidence: 99%